Problem Solving Management of Principal in Improving School’s Quality - Suparman, Asep; Macariola, Julie Simon (PPSDP International Journal of Education, 2022)
The purpose of writing in this paper is to present a description of innovations regarding the application of problem solving management by principals in an effort to improve school achievement. The method used in this research is descriptive qualitative. This research is useful in the field of principal management in managing schools that have limited infrastructure and students who are categorized as less, both economically and academically. Based on the results and discussion, it can be concluded that the application of problem solving management by principals can improve school achievement marked by the number of awards received by schools, increased public interest and the existence of other schools that have comparative studies in schools. The novelty in this study is the managerial pattern of the principal in dealing with various kinds of complex problems but is still able to improve the quality of the school.